1998
DOI: 10.1146/annurev.publhealth.19.1.73
|View full text |Cite
|
Sign up to set email alerts
|

CHEMOPREVENTION OF LUNG CANCER: The Rise and Demise of Beta-Carotene

Abstract: Beta-carotene and retinoids were the most promising agents against common cancers when the National Cancer Institute mounted a substantial program of population-based trials in the early 1980s. Both major lung cancer chemoprevention trials not only showed no benefit, but had significant increases in lung cancer incidence and in cardiovascular and total mortality. A new generation of laboratory research has been stimulated.Rational public health recommendations at this time include: 1. Five-A-Day servings of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(87 citation statements)
references
References 100 publications
(98 reference statements)
0
83
1
3
Order By: Relevance
“…However, the ATBC and CARET studies found, paradoxically, that β-carotene supplementation increased the incidence of lung cancer, thereby refuting the conclusions based on the observational studies. 15,19 Similarly, meta-analyses of vitamin E trials 20,21 refuted the cohort studies suggesting that increased vitamin E intake would reduce the risk of cardiovascular diseases in large population groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ATBC and CARET studies found, paradoxically, that β-carotene supplementation increased the incidence of lung cancer, thereby refuting the conclusions based on the observational studies. 15,19 Similarly, meta-analyses of vitamin E trials 20,21 refuted the cohort studies suggesting that increased vitamin E intake would reduce the risk of cardiovascular diseases in large population groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, high serum β-carotene levels have been associated with a decrease in incidence of cancer, including lung cancer, in humans (Mayne, 1996;Ziegler et al, 1996). However, the ATBC study and CARET trials (ATBC Study group, 1994;Omenn et al, 1996a;1996b;Omenn, 1998) unexpectedly revealed that heavy smokers (at least 1 package/day for 36 years on average) receiving long-term β-carotene (20 mg/day) supplementation (ATBC) or β-carotene (30 mg/day) + retinol (25 000 International Unit (IU) vitamin A) supplementation (CARET), showed increased rather than decreased incidences of lung cancer.…”
Section: Terms Of Reference As Provided By European Commissionmentioning
confidence: 99%
“…Examples are antioxidant vitamins (beta-carotene, C, E), vitamin A and other retinoids, folic acid, and inducers of glutathione. 11,12 For infectious agents, vaccines can be highly effective preventive interventions. And for environmental and occupational risk reduction, it is feasible to monitor emissions, exposures, and subclinical and clinical effect rates after actions are taken.…”
Section: A Golden Age For the Public Health Sciencesmentioning
confidence: 99%